Impact of shoulder as a road safety countermeasure: A literature Review: Dampak bahu jalan sebagai penanggulangan keselamatan jalan: Tinjauan pustaka - Gyanendra Singh (Journal of Multidisciplinary Science, 2023)
The review included 31 studies of which 14 were before-after analysis, 13 used cross-section analysis, seven case-control, a cohort analysis and a review. Some studies used more than one type of study design for analysis. Twenty seven studies were conducted in the USA, one in South Korea, France and Australia each and no studies from low or middle income countries. The evidence from these studies indicate mixed results for influence of shoulder as an intervention on crash outcome. Most studies indicate that increase in shoulder width up to 8 feet leads to reduction in crash outcomes whereas shoulder width exceeding 8ft leads to increase in crashes or no crash reduction is observed. Narrow shoulders show higher crash rates as compared to wider shoulders. Studies also report that upgradation of unpaved shoulders to stabilized or composite shoulder type also reduces crash outcomes. The results of this review suggest that shoulder implementation, increasing shoulder width up to 8ft and upgrading shoulder type may prove to be a promising countermeasure for reducing all types of road traffic crashes. However, the evidence of effectiveness of these countermeasuresmay not be replicable in other parts of the world, hence, further evaluations are needed.